PROFIL PEDAGANG IKAN SEGAR DI PASAR PINASUNGKULAN KELURAHAN KAROMBASAN UTARA KECAMATAN WANEA KOTA MANADO - Wakerkwa, Tion; Manoppo, Victoria E.N.; Durand, Swenekhe S.; Sondakh, Srie J.; Aling, Djuwita R.R.; Sinjal, Chatrine A. (Universitas Sam Ratulangi, 2021)
AbstractThis study aims to analyze the profile of fresh fish traders in the Pinasungkulan market, North Karombasan Village, Wanea District, Manado City. The method used is a survey method. The population in this study is fresh fish traders. The data consists of primary data and secondary data. Primary data is done through observation, interviews guided by questionnaires, while secondary data is obtained indirectly, namely in the form of evidence, historical records or reports that have been compiled in the library. The analysis used in this research is descriptive quantitative analysis and descriptive qualitative.The age of the respondent is at the age of less than 65 years, which is in the productive age. The age of the traders who are still of productive age so that they can survive selling even though they are rarely buyers or when the number of buyers increases. Fresh fish traders have junior high school education (50%), high school (30%), and bachelor degree (10%) and do not go to school (10%). Number of family members 1-3 people and there are more than 3 family members.The income of fresh fish traders varies, namely Rp. 250,000 per day (30%), and Rp. 500,000 per day (50%), and greater than Rp. 500,000 (20%). Expenditures in the form of transportation expenses of Rp. 10,000 per day and do not spend money on transportation because it is walking from home to the market location. Fresh fish traders who sell for more than 10 years are the largest number. Initial business capital to sell their own capital or joint venture with family members. Places of sale, as much as 80% are self-owned and as much as 20% are only rented.Keywords: Socio-Economic Studies, Fresh Fish, Pinasungkulan Market AbstrakPenelitian ini bertujuan untuk menganalisis profil pedagang ikan segar di pasar Pinasungkulan Kelurahan Karombasan Utara Kecamatan Wanea Kota Manado. Metode yang digunakan adalah metode survey. Populasi pada penelitian ini ialah pedagang ikan segar. Data terdiri atas data primer dan data sekunder. Data primer dilakukan melalui observasi, wawancara yang dipandu dengan kuesioner, sedangkan data sekunder diperoleh secara tidak langsung, yaitu berupa bukti, catatan atau laporan historis yang telah tersusun di perpustakan. Analisis yang digunakan dalam penelitian ini adalah analisis deskriptif kuantitatif dan deskriptif kualitatif.Umur responden berada pada usia lebih kurang dari 65 tahun yaitu berada pada produktif. Umur para pedagang yang masih usia produktif sehingga mereka bisa bertahan berjualan walaupun jarang pembeli ataupun pada saat jumlah pembeli meningkat. Pedagang ikan segar memiliki pendidikan SMP (50%), SMA (30%), Sarjana (10%) dan tidak bersekolah (10%). Jumlah Anggota keluarga 1 – 3 orang dan ada yang lebih dari 3 anggota keluarga.Pendapatan pedagang ikan segar bervariasi, yaitu Rp. 250.000 per hari (30%), dan Rp. 500.000 per hari (50%), dan lebih besar dari Rp. 500.000 (20%). Pengeluaran berupa pengeluaran transportasi sebesar Rp. 10.000 per hari dan tidak mengeluarkan uang transportsi karena berjalan kaki dari rumah ke lokasi pasar. Para pedagang ikan segar yang berjualan lebih dari 10 tahun merupakan jumlah terbesar. Modal awal usaha untuk berjualan modal sendiri ataupun patungan bersama anggota keluarga. Tempat jualan, sebanyak 80% adalah milik sendiri dan sebanyak 20% hanya sewa.Kata Kunci: Kajian Sosial Ekonomi, Ikan Segar, Pasar Pinasungkulan